Digitally integrated Cooperative Learning Models to Enhance Student’s Creativity: Comparative Analysis Across Creativity Dimensions - Suparmi, Suparmi; Sukmawati, Fatma; Santosa, Eka Budhi; Cahyono, Budi Tri; Prihatin, Relly (Universitas Negeri Makassar, 2025)
In the 21st century, students’ creativity needs to be developed to confront global change. This study aims to provide a comprehensive overview of Cooperative learning to enhance on students’ creativity across all dimensions. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) was used as the methodology. The results showed that cooperative learning can foster dimensions of creativity: fluency, flexibility, originality, and elaboration. Specifically, fluency is supported by Student Teams Achievement Division, Think-Pair-Share and Numbered Heads Together, and the integration of digital gamification with Cooperative Learning. Flexibility is supported by Jigsaw/Group Investigation and the integration of digital gamification with cooperative learning. Originality is supported by Think-Pair-Share and Numbered Heads Together, Cooperative-Project Based learning, and the integration of digital gamification with cooperative learning. Elaboration strengthens Student Teams Achievement Division, Jigsaw/Groups Investigation, and Cooperative-Project Based learning. Mediators supporting cooperative learning include teacher competence, classroom climate, task design, evaluation, and digital access. The new of this study are student orientation, integration of cooperative learning with digitalization, and model comparison. The conclusion is that cooperative learning can enhance students’ creativity through fluency, flexibility, originality, and elabotation, which are strengthened by digital integration and supportive classroom factor.